Organske spremembe in motnje prehranjevanja v starosti - Kobentar, Radojka (Obzornik zdravstvene nege, 2000)
The article describes the most common organic changes of digestive system in old age. Short rules of healthy nutrition are stated, as well as causes of nutritional problems in old age and their most common symptoms. Some problems related to nutritional disorders are described, and their treatment, soothing and elimination by means of certain procedures and remedies. Feeding through nasogastric tube or in the form of intravenous infusion are also described.
Keywords: Aged; Colitis, ulcerative; Colonic neoplasms; Constipation; Digestive system diseases; Duodenal ulcer; Esophageal diseases; Etiology; Hernia, hiatal; motnje; Neuralgia; Nutrition disorders; prehranjevanje; spremembe; starostniki; Stomach diseases; Therapy; Tremor; Xerostomia